Evaluation of The Quality of Physical Assets Batu Mahpar Geopark Recreation Park in Tasikmalaya District - Purwihartuti, Koernia; Dwiyanto, Lutfi; Angestiwi, Tiafahmi; Karnawati, Hennidah; Guterres, Alexandre Desousa (Universitas Islam Sultan Agung Semarang, 2023)
Batu Mahpar Geopark Recreation Park has tourist attractions which include rock expanses, five waterfalls, campsites, mini zoos, outbound rides, museums, interpretation boards, outdoor swimming pools, and photo spots. However, there are a number of indications of problems related to the quality of physical assets, including the difficulty of finding public transportation, car parks, information centers, visitor needs kiosks and souvenir kiosks, there are ten photo spots that are damaged, trash cans are not separated by type of waste, put together places for ablution between men and women, there are footpaths covered with wild plants, and the cell phone signal is unstable. Based on the indications of these problems, it is necessary to conduct research that aims to evaluate the quality of Batu Mahpar's physical assets including the availability and condition of assets which consist of four dimensions including tourist attractions, accessibility, supporting facilities, and infrastructure. This research uses descriptive methods with qualitative and quantitative approaches. Data collection techniques used include observation, interviews, and questionnaires. The results of the evaluation show that the dimensions of tourist attractions, supporting facilities and infrastructure are good quality, while the accessibility dimensions have sufficient quality. The average value of the quality of physical assets resulting from the four dimensions is 64.66%. This means that Batu Mahpar's physical assets are of sufficient quality.Keywords: Facilities, Infrastructure, Physical Assets, Quality Evaluation, Tourism